2022
DOI: 10.1029/2022jd037050
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt Change in the Lower Thermospheric Mean Meridional Circulation During Sudden Stratospheric Warmings and Its Impact on Trace Species

Abstract: Based on the hourly output from the 2000–2014 simulations of the National Center for Atmospheric Research's vertically extended version of the Whole Atmosphere Community Climate Model in specified dynamics configuration, we examine the roles of planetary waves (PWs), gravity waves, and atmospheric tides in driving the mean meridional circulation (MMC) in the lower thermosphere (LT) and its response to the sudden stratospheric warming phenomenon with an elevated stratopause in the northern hemisphere. Sandwiche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 58 publications
(148 reference statements)
1
16
0
Order By: Relevance
“…During weak stratosphere polar vortex time periods, the residual meridional circulation in the Northern Hemisphere has southward anomalies between 10 −1 and 10 −2 hPa (65–80 km) and northward anomalies at higher altitudes (10 −3 to 10 −5 hPa, 95–120 km). The spatial structure and the magnitude of the anomalies are consistent with the anomalies that occur during SSWs (Orsolini et al., 2022). The anomalies stretch into the Southern Hemisphere with decreasing amplitude and the boundary between southward and northward anomalies increasing in altitude from the Northern to Southern Hemispheres.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…During weak stratosphere polar vortex time periods, the residual meridional circulation in the Northern Hemisphere has southward anomalies between 10 −1 and 10 −2 hPa (65–80 km) and northward anomalies at higher altitudes (10 −3 to 10 −5 hPa, 95–120 km). The spatial structure and the magnitude of the anomalies are consistent with the anomalies that occur during SSWs (Orsolini et al., 2022). The anomalies stretch into the Southern Hemisphere with decreasing amplitude and the boundary between southward and northward anomalies increasing in altitude from the Northern to Southern Hemispheres.…”
Section: Resultssupporting
confidence: 85%
“…The changes in wave forcing during SSWs, including from gravity waves, planetary waves, and tides, alter the mean circulation of the MLT. During SSWs, the MLT circulation is characterized by enhanced clockwise and anti‐clockwise circulation patterns in the Northern and Southern Hemispheres, respectively (Limpasuvan et al., 2016; Miyoshi et al., 2015; Orsolini et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Previous modeling studies (e.g., Miyoshi et al, 2015;Orsolini et al, 2022;Wang et al, 2022;J. Zhang et al, 2021 suggest that the climatological direction of the mesosphere-lower thermosphere (MLT) mean meridional circulation (MMC), characterized by upwelling in the middle winter latitudes, equatorward flow near ∼100-120 km, and poleward flow near ∼80-100 km, reverses following the onset of SSWs.…”
mentioning
confidence: 99%
“…Previous modeling studies (e.g., Miyoshi et al, 2015;Zhang J. et al, 2021Zhang J. et al, , 2022Orsolini et al, 2022;Wang et al, 2022) suggest that the climatological direction of the mesosphere-lower thermosphere (MLT) mean meridional circulation (MMC), characterized by upwelling in the middle winter latitudes, equatorward flow near ∼100-120 km, and poleward flow near ∼80-100 km, reverses following the onset of SSWs. Ground-totopside model of Atmosphere and Ionosphere for Aeronomy (GAIA) model simulations from Miyoshi et al (2015) revealed that MMC reversed in the lower thermosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Ground-totopside model of Atmosphere and Ionosphere for Aeronomy (GAIA) model simulations from Miyoshi et al (2015) revealed that MMC reversed in the lower thermosphere. More recently, Orsolini et al (2022) used the Whole Atmosphere Community Climate Model with thermosphere and ionosphere eXtension (WACCM-X) in the specified dynamics configuration to show that the lower thermospheric mean meridional circulation reverses for about 10 days following the onset of elevated stratopause events in the northern hemisphere largely driven by westward-propagating planetary waves. Important impacts on MLT mean circulation have also been reported observationally (e.g., Oberheide, 2022) including enhancements of both eastward and westward directed flow associated with wave dissipation.…”
Section: Introductionmentioning
confidence: 99%